Can "Austrian economics" provide a new approach to environmental policy? - Ferry Stocker (Fondazione Eni Enrico Mattei (FEEM), 1997)
Whereas 'traditional environmental economics' - considering pervasive 'market failure' in the form of negative externalities as the root cause of the problem of environmental degradation - argues for specific government intervention in the market process via a host of different measures to correct that 'perceived failure', this paper sets out to challenge that somewhat superficial view. At least since the seminal contribution of Coase it has become clear that it is the 'underlying institutional structure' of the market economy, the structure of the 'property rights', that determines the 'degree of efficiency' in a particular 'real economy'. However, taking the dynamic and more encompassing view of North the pivotal question becomes asking about the determinants of the evolution of appropriate institutions to protect the environment and what can be done to foster that development. This calls for a 'retreat' of the pervasively meddling state in this respect, highlights the pivotal role of the Schumpeterian entrepreneur in a typical 'Hayekian setting' and constitutes a new - an Austrian - approach towards environmental policy.
Keywords: 330; Property rights; institutional evolution; entrepreneur; Umweltpolitik; Umweltökonomik; Österreichische Schule; Neue Institutionenökonomik; Eigentumsrecht; Theorie